Elevated pre-transplant pulmonary vascular resistance is associated with early post-transplant atrial fibrillation and mortality - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Schmack, Bastian; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Dösch, Andreas; Katus, Hugo; Ehlermann, Philipp (ESC heart failure, 2020)
Aims Severely elevated pre-transplant pulmonary vascular resistance (PVR) has been linked to adverse effects after heart transplantation (HTX). The impact of a moderately increased PVR before HTX on post-transplant outcomes remains uncertain. The aim of this study was to investigate the effects of an elevated pre-transplant PVR ≥ 300 dyn·s·cm−5 (≥3.75 Wood units) on outcomes after HTX. Methods and results This observational retrospective single-centre study included 561 patients receiving HTX at Heidelberg Heart Center between 1989 and 2015. Patients were stratified by degree of pre-transplant PVR. Analyses covered demographics, post-transplant medication, mortality and causes of death after HTX, early post-transplant atrial fibrillation (AF), and length of the initial hospital stay after HTX. Ninety-four patients (16.8%) had a PVR ≥ 300 dyn·s·cm−5 (≥3.75 Wood units). These patients had a higher rate of early post-transplant AF [20.2 vs. 10.7%, difference: 9.5%, 95% confidence interval (CI): 0.9-18.1%, P = 0.01] and an increased 30 day post-transplant mortality (25.5 vs. 6.4%, hazard ratio: 4.4, 95% CI: 2.6-7.6, P < 0.01), along with a higher percentage of death due to transplant failure (21.2 vs. 4.1%, difference: 17.1%, 95% CI: 8.7-25.5%, P < 0.01). Multivariate analysis revealed a PVR ≥ 300 dyn·s·cm−5 (≥3.75 Wood units) as a significant risk factor for increased 30 day mortality after HTX (hazard ratio: 4.4, 95% CI: 2.5-7.6, P < 0.01). Kaplan-Meier estimator showed a lower 2 year survival after HTX (P < 0.01) in patients with a PVR ≥ 300 dyn·s·cm−5 (≥3.75 Wood units). Conclusions Elevated pre-transplant PVR ≥ 300 dyn·s·cm−5 (≥3.75 Wood units) is associated with early post-transplant AF and increased mortality after HTX.
Gesehen am 14.04.2020